The Formal Flaws of the Achievement Test Paper and Their Impact on Visual Processing Among General Education Students - Altoum, Ibrahim Abdullah (Journal of Educational and Psychological Sciences, 2025)
This research aims to analyze the common formal flaws in test papers used in general education, examining their prevalence and impact on students’ ability to read and comprehend questions, which may affect their academic performance. The study also seeks to identify the relationship between these flaws and students’ levels of concentration and attention during answering, in addition to exploring the visual impact differences of these flaws according to educational stage or age. The research adopted a descriptive-analytical methodology and analyzed the responses of a sample of 150 students from elementary, middle, and secondary school levels. The results revealed that elementary students achieved the highest mean score (14.6), compared to middle (13.6) and secondary (12.4) students, indicating that test papers may be more suitable for younger students. Specifically, the dimension of fonts and typography scored a mean of (3.8) in elementary school, which decreased to (3.8) in middle and (3.2) in secondary school, highlighting the importance of clear printing for younger students. As for page organization, the means ranged between (3.7) for elementary and (3.3) for secondary, while the general format and visual clarity dimension recorded the lowest mean (2.9) in secondary school. The study recommended improving the quality of achievement tests through regular review and enhancing integration between exam questions and review questions.